(untitled) (Journal of Laboratory Animal Science, 2024)
Sanitization is an important activity performed in the laboratory animal facilities and periodical assessment of sanitization provides confidence in surface cleanliness as well as health status of animals in the vivarium. The primary objective was to evaluate routine disinfection and/or sanitization practices upon verifying the adenosine triphosphate (ATP) bioluminescence method, which further expressed as relative light units (RLU), a relatively easy and rapid method to interpret results within a minute after the swab sampling performed on any surface. A five-year data compilation showed that RLU values were within the in-house acceptable limits of animal rooms sampled from racks, isolators, doors, trolleys, cage changing stations, tables, walls and cage accessories. However, some of the materials such as racks and trolleys of high-traffic areas showed a significant increase in RLU values due to organic matters that might be present on the equipment surfaces but recorded values were well within the limits set by the facility. Additionally, contact plates were also used as confirmatory method to evaluate microbial monitoring in animal rooms including cage accessories and further historical values of RLU provided confidence to increase monthly contact plate sampling interval to a quarterly basis and followed as per the schedule. Moreover, representative samples from incoming animals were screened by microbial monitoring at regular intervals during the quarantine period and active sentinel samples also screened for serology or PCR as part of comprehensive health monitoring program. In conclusion, ATP method can be used to assess the real-time effectiveness of sanitization practices in vivarium as it provides immediate feedback to animal care personnel that enables corrective actions; hence the ATP bioluminescence is continued as one of the complementary methods at our laboratory animal facility.